Arritmia ventricular casi fatal asociada a uso de psicofármacos - Amado-Tineo, José (2019)
The use of psychotropic drugs is increasingly frequent due to emerging problems such as depression. We present the case of a 47-year-old woman who received antidepressant treatment (fluoxetine and levomepromazine) and arrived at the emergency room because lost consciousness in her home, evidencing two episodes of pulseless ventricular tachycardia during her hospital stay that responded satisfactorily to defibrillation and advanced cardiopulmonary resuscitation. The prolongation of the QT interval associated with the use of antidepressants and antipsychotics, as well as their risk factors, is discussed. Finally, it is important to have on mind the relationship between psychotropic drugs and potentially fatal ventricular arrhythmias, making it necessary to perform an electrocardiogram to these patients who consult the emergency room.